2018
DOI: 10.1507/endocrj.ej17-0445
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide ameliorates rat myocardial fibrosis induced by thyroxine through PI3K/AKT signaling pathway

Abstract: This study aims to investigate the role and regulatory mechanism of the Hydrogen sulfide (HS) in amelioration of rat myocardial fibrosis induced by thyroxine through interfering the autophagy via regulating the activity of PI3K/AKT1 signaling pathway and the expression of relative miRNA. 40 adult male SD rats were randomly divided into 4 groups (n = 10): the control group, the thyroxine model group (TH group), the model group with HS intervention (TH + HS group) and the normal group with HS intervention (HS gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Yang et al [ 25 ] reported that miRNA-214 suppresses oxidative stress in diabetic nephropathy via the ROS/Akt/mTOR signaling pathway and uncoupling protein2. Liu et al reported that miR-214 could regulate autophagy through the PI3K/AKT signalling pathway in the rat model of myocardial fibrosis [ 26 ]. Gong et al reported that Oridonin relieved hypoxia-caused apoptosis and autophagy via adjusting the PI3K/AKT/mTOR pathway through the enhancement of miR-214 in H9C2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [ 25 ] reported that miRNA-214 suppresses oxidative stress in diabetic nephropathy via the ROS/Akt/mTOR signaling pathway and uncoupling protein2. Liu et al reported that miR-214 could regulate autophagy through the PI3K/AKT signalling pathway in the rat model of myocardial fibrosis [ 26 ]. Gong et al reported that Oridonin relieved hypoxia-caused apoptosis and autophagy via adjusting the PI3K/AKT/mTOR pathway through the enhancement of miR-214 in H9C2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although a role in autophagy has not been reported for miR-21, it appears to protect against cardiac I/R injury by its ability to inhibit excessively augmented autophagic pathways [116]. Consistent with the potential synergy between miR-146 and miR-21, it was recently reported that upregulation of miR-21 is associated with decreased autophagy in myocardial tissues [117].…”
Section: Micrornas (Mirnas)mentioning
confidence: 97%
“…CSE is the key enzyme of endogenous H 2 S source in cardiovascular system ( Zheng et al., 2018 ), CBS and 3MST also participate in the production of endogenous H 2 S in peripheral vascular tissue ( Prabhudesai et al., 2018 ). Our research group has confirmed that H 2 S could antagonize myocardial fibrosis by regulating multiple intracellular signaling pathways ( Liu et al., 2018a ; Liu et al., 2018b ), however the internal regulatory mechanism of H 2 S is very complex, which is still not clear until now. Therefore, it is of great significance to further explore the myocardial protection mechanism of H 2 S. This study observed that exogenous H 2 S can activate endogenous H 2 S-producing enzyme CSE and improve STZ-induced myocardial fibrosis and MMPs/TIMP1 imbalance in diabetic rats.…”
Section: Discussionmentioning
confidence: 96%